2021
DOI: 10.1186/s12879-021-05984-1
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up study on serum cholesterol profiles and potential sequelae in recovered COVID-19 patients

Abstract: Background COVID-19 patients develop hypolipidemia. However, it is unknown whether lipid levels have improved and there are potential sequlae in recovered patients. Objective In this follow-up study, we evaluated serum lipidemia and various physiopathological laboratory values in recovered patients. Methods A 3–6 month follow-up study was performed between June 15 and September 3, 2020, to examine seru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 31 publications
2
23
0
5
Order By: Relevance
“… 23 These differences were observed in TC, phospholipids and their respective particles and sub‐particles, and they were reminiscent of those observed during the acute phase of COVID‐19 disease, which were associated with liver dysfunction. 15 , 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 These differences were observed in TC, phospholipids and their respective particles and sub‐particles, and they were reminiscent of those observed during the acute phase of COVID‐19 disease, which were associated with liver dysfunction. 15 , 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…Statistical differences between cohorts are represented as **** (p < 0.0001) These differences were observed in TC, phospholipids and their respective particles and sub-particles, and they were reminiscent of those observed during the acute phase of COVID-19 disease, which were associated with liver dysfunction. 15,24,25 The RE_II sub-cohort showed specific features, including an upregulation of many lipoprotein subfractions that were found to be depleted in acute COVID-19 patients. Indeed, the profile shown in Figure S3 suggested that the lipoprotein metabolism for the RE_II sub-cohort rebooted from the disease, but still does not show full recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that hypolipidemia in hospitalized COVID-19 patients at the admission and the decrease in lipid levels were associated with the severity of the symptoms (6)(7)(8)(9)(10)12,14,15). In one of the first studies early in the pandemic, patients with COVID-19 develop hypolipidemia as early as when they have mild symptoms and a reduction of lipid levels in patients with COVID-19 has an association with the severity of the symptoms (23).…”
Section: Discussionmentioning
confidence: 99%
“…LDL-C, TC and HDL-C concentrations significantly decreased in COVID-19 patients (6)(7)(8)(9)(10). Although most of the studies were in hospitalized patients, literature on lipid profiles during follow-up in discharged COVID-19 (post-COVID) patients is rare (11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The anti-fibrotic effect of statins seems to be very interesting from the point of view of complications of SARS-CoV-2 infection (especially in the long-COVID-19 syndrome). In a study by Li et al which included 107 patients with COVID-19, it was shown that after 3–6 months after recovery, some of them may develop pulmonary fibrosis [ 85 ]. In an experimental study using mice and human lung fibroblasts/myofibroblasts, the effect of atorvastatin on the processes of fibrosis was assessed.…”
Section: Introductionmentioning
confidence: 99%